2018
DOI: 10.14814/phy2.13697
|View full text |Cite
|
Sign up to set email alerts
|

Older men display elevated levels of senescence-associated exercise-responsive CD28nullangiogenic T cells compared with younger men

Abstract: Aging is associated with elevated cardiovascular disease risk. As a result of aging, endothelial dysfunction develops, partly due to a reduction in vascular regenerative ability. CD31+ T cells (angiogenic T cells; TANG) possess highly angiogenic capabilities; however, these cells are significantly reduced in older populations. In addition, older populations possess significantly higher senescent and highly differentiated T‐cell levels in circulation, and these are reported to be highly exercise responsive. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 41 publications
(115 reference statements)
0
24
0
3
Order By: Relevance
“…The results of the present study are similar to those observed following a 10 km treadmill time-trial (Ross et al 2016), where increases in circulating CD3 + CD31 + , CD8 + CD31 + and CD4 + CD31 + cells were reported immediately post-exercise with values back to pre-exercise levels at 1 h post-exercise. Two other studies (Ross et al 2018a;Ross et al 2018b) have reported that the response of these TANG cells to continuous exercise is age-dependent, with an impaired ingress and egress of these cells in older participants. The 45 min duration of exercise in CONTEX is similar to that in the 10 km timetrial.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The results of the present study are similar to those observed following a 10 km treadmill time-trial (Ross et al 2016), where increases in circulating CD3 + CD31 + , CD8 + CD31 + and CD4 + CD31 + cells were reported immediately post-exercise with values back to pre-exercise levels at 1 h post-exercise. Two other studies (Ross et al 2018a;Ross et al 2018b) have reported that the response of these TANG cells to continuous exercise is age-dependent, with an impaired ingress and egress of these cells in older participants. The 45 min duration of exercise in CONTEX is similar to that in the 10 km timetrial.…”
Section: Discussionmentioning
confidence: 93%
“…Increases in CAC were evident immediately post-exercise with counts typically back to pre-exercise values at the 2 h timepoint. Exercise also elicited a qualitative change in CAC, evidenced by the increase in CXCR4 expression on TANG at the 24 h timepoint, To date, only a limited number of studies (Lansford et al 2016;Ross et al 2018a;Ross et al 2016;Ross et al 2018b;Shill et al 2016) examining the effects of acute exercise on circulating TANG have been undertaken. The results of the present study are similar to those observed following a 10 km treadmill time-trial (Ross et al 2016), where increases in circulating CD3 + CD31 + , CD8 + CD31 + and CD4 + CD31 + cells were reported immediately post-exercise with values back to pre-exercise levels at 1 h post-exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 28% of the studies did not describe whether the measurement was done on frozen or fresh cells ( 15 , 22 , 23 , 26 , 28 31 , 49 , 50 ); 33% of the articles did not report the number of cells used in each experiment ( 15 , 17 , 18 , 20 , 22 , 24 26 , 28 , 31 , 35 , 36 ), while only 31% clearly described the antibodies with fluorochrome and clone used ( 15 , 21 , 22 , 28 , 31 , 39 , 41 , 43 , 44 , 46 , 48 ). The factor with the highest risk of bias is the clarity in the presentation of the results, since only 25% of the studies reported measures of central tendency ( 16 , 27 , 33 , 37 , 41 , 42 , 47 , 48 , 50 ). Most of the studies reported only the graphics and p-value, thus making it difficult to quantitatively compare results and rate evidence.…”
Section: Resultsmentioning
confidence: 99%